KOMUNIKASI ORGANISASI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN SUMEDANG - puja puspayani (LPPM UNSAP & FISIP UNSAP, 2025)
Objective researcher do is For know condition from communication organization in the disaster management agency disaster area regency sumedang .Methods used in study This is method study qualitative . Where study This based on philosophy postpositivism , which is used For research on conditions object natural , where researcher act As a key instrument , data collection techniques are carried out in a way triangulation ( combination ), data analysis is inductive , and results study qualitative more emphasize meaning from on generalization . The technique used intaking sample is with using purposive sampling, namely taking sample based on needs . Then sample taken in study This that is as many as 4 people.Informant in study This are the implementers who are considered own authority , information , and involved in communication organization in the disaster management agency disaster area regency sumedang .Based on results research , can researcher describe that communication organization in the disaster management agency disaster area regency sumedang can rated good , but Still there is problem about flow communication up , down , and horizontal communication . Obstacles found covering lack of facilities and infrastructure , control technique communication is not optimal, and constraint physical . For overcome obstacle said , BPBD carried out effort like improvement facility communication , training skills communication , and improvement system internal coordination . Research This confirm that communication effective organization very important For support BPBD performance in countermeasures disaster in a way fast , precise , and coordinated.